1993
DOI: 10.1016/0014-5793(93)80515-v
|View full text |Cite
|
Sign up to set email alerts
|

Probing the phalloidin binding site of actin

Abstract: Phallotoxins form tight complexes with filamentous actm and stabilize the polymer against shearing stress. In the present study a phalloidin derivative containing a thiol-capturmg moiety was prepared and reacted with single thiol groups of monomeric muscle actin. Sites of attachment in the protein were Cys-374 next to the C-terminus and Cys-10, close to the N-terminus; the latter was recently shown to be uncovered during a slow but reversible conformational transition occurring in ADP-G-actin. Phalloidin bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…To decrease the effect of actin monomers the actin concentration was adjusted to a relatively large value, 30 M. Furthermore, the FRET efficiency was also measured in the presence of phalloidin, so that the undesired effect of the contribution of actin monomers on the measured fluorescence parameters could be estimated. The stabilizing effect of phalloidin on actin filaments was described earlier by using a number of experimental methods (20,35,(52)(53)(54)(55)(56). It was shown that phalloidin decreased significantly the rate of monomer dissociation and shifted the monomer-filament equilibrium toward the filamentous form.…”
Section: Discussionmentioning
confidence: 95%
“…To decrease the effect of actin monomers the actin concentration was adjusted to a relatively large value, 30 M. Furthermore, the FRET efficiency was also measured in the presence of phalloidin, so that the undesired effect of the contribution of actin monomers on the measured fluorescence parameters could be estimated. The stabilizing effect of phalloidin on actin filaments was described earlier by using a number of experimental methods (20,35,(52)(53)(54)(55)(56). It was shown that phalloidin decreased significantly the rate of monomer dissociation and shifted the monomer-filament equilibrium toward the filamentous form.…”
Section: Discussionmentioning
confidence: 95%
“…4). Phalloidin was an effective indicator of F-actin, reduced the rate of actin filament depolymerization, and prevented conversion of F-actin to G-actin [46]. It is not clear how the F-actin became distributed throughout the vesicle, since non-filamentary actin is expected to be in the G form and unavailable for phalloidin binding.…”
Section: Gpmv Actin Contentsmentioning
confidence: 99%
“…After further washing, gels were incubated with rhodamine phalloidin (Molecular Probes, Eugene, OR; 1:50 dilution). After a final washing in phosphate buffer, gels were mounted on glass slides with glycerol and sealed with coverslips [Faulstich et al, 1993]. Confocal imaging of cytoskeletal actin was performed using the Noran-Odyssey confocal laser scanning microscope.…”
Section: Cell Morphologymentioning
confidence: 99%